2013
DOI: 10.1080/87568225.2013.798225
|View full text |Cite
|
Sign up to set email alerts
|

University Mental Health Professionals in Puerto Rico: Suicide Experiences, Attitudes, Practices, and Intervention Skills

Abstract: At a university health clinic, 46 medication abortion cases, presented between 2006 and 2009, were reviewed. Medication abortion involves the drugs mifepristone and misoprostal. This review showed that medication abortion within a student health care setting was generally safe: 85 percent of the cases were successfully completed without the need for uterine aspiration, and the patients who needed uterine aspiration were treated with a manual vacuum aspiration device. Only one patient had to go to the emergency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…They can be among the first to screen and intervene for suicide risk as they may be in close contact with suicidal individuals and therefore have the opportunity to interrupt an ongoing suicidal process [5,6]. Front-line health professionals, such as general practitioners, mental health professionals and emergency department staff, report that targeted education and training in suicide prevention would be helpful [3,7,8,9,10]. Furthermore, a broad range of both health and community professionals appear to benefit from education and training interventions [3,11,12,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…They can be among the first to screen and intervene for suicide risk as they may be in close contact with suicidal individuals and therefore have the opportunity to interrupt an ongoing suicidal process [5,6]. Front-line health professionals, such as general practitioners, mental health professionals and emergency department staff, report that targeted education and training in suicide prevention would be helpful [3,7,8,9,10]. Furthermore, a broad range of both health and community professionals appear to benefit from education and training interventions [3,11,12,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Despite these socioeconomic risk factors, suicide is primarily viewed as a moral failure of individuals, e.g., as a sign of "weakness," "cowardice," "badness," "mental illness," or "admission of failure" [12,24,40], This perspective has become normalized in many societies, and reflects discomfort with and avoidance or rejection of the topic [24,40]. This view of suicide has been documented at all socioecological levels, including individuals who self-stigmatize [24,40,41]; families, peers, and other social groups [9,24]; community [1]; policy (e.g., insurance companies, policies, and personal attitudes affecting coroners' official declarations of cause of death; Noble, 2010 [46];); and media messages, including mass and social media [21,25,26].…”
Section: A Social Justice Frameworkmentioning
confidence: 99%
“…In the United States alone, there are approximately 115,580 mental health counselors and 607,300 social workers (Bureau of Labor Statistics, 2016a, 2016b. Unfortunately, research has shown that clinicians on the forefront of this issue often lack the suicide education necessary to treat such an increasingly high-risk population (Jiménez-Chafey, Serra-Taylor, & Irizarry-Robles, 2013). In the next five years, approximately one million veterans will leave military service and return to civilian life (U.S. Government Accountability Office, 2019), and studies have shown that military veterans are at an increased risk for suicide.…”
Section: Introductionmentioning
confidence: 99%
“…Accurately and confidently assessing a client's suicide risk should be a graduate program requirement for mental health clinicians; however, current research suggests a gap between clinical practice and suicide-assessment knowledge and selfefficacy (Jiménez-Chafey et al, 2013). Trainings that teach suicide-assessment theories and skills, which tend to be economical and efficient, have helped to close this gap (Cross, Matthieu, Lezine, & Knox, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation